The practice of Portuguese traditional music in primary schools - Boal-Palheiros, G. (2018)
Social and technological changes have made the musics of the world available to most people. Educators agree on the value of traditional music (folk, popular, ethnic, world), in school music education. The guidelines of the music curriculum of basic education in Portugal include learning traditional music, knowing the musical patrimony and developing a national identity. Our teaching experience suggests that children often reject traditional music in schools, despite existing rich musical traditions in everyday life. The present study has investigated the practice of Portuguese traditional music in primary schools in Portugal, by focusing on the activities carried out by 30 generalist teachers and their pupils, and on the teachers’ views on children’s attitudes towards traditional music. The results of the questionnaire carried out with the teachers indicate that Portuguese traditional music is rarely practiced in primary schools and few teachers include it in their lessons. However, a positive result is that children are receptive to learning this musical style, and whenever they have opportunities to learn it, their general motivation for school music does increase.